(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The purpose of this study is to separate the concept of description from other types of research and to determine the semantic content when it stands alone; conduct a philosophical analysis of the concept of description and reflect the path of the concept of description in the history of philosophy, dividing it into parts. In addition, the novelty of this work is the descriptive definition of the epistemological, ontological and methodological diversity of description